Exploring the Preferences of Consumers’ Organic Products in Aspects of Sustainable Consumption: The Case of the Polish Consumer - Wojciechowska-Solis, Julia; Barska, Anetta (Agriculture (Basel), 2021)
The dynamically developing trend of sustainable consumption is manifested, among others, by the growing interest in organic products on the part of consumers. The aim of this article was to identify the behavior of Polish consumers in the market of organic products and to establish a link between their environmental awareness and willingness to buy organic products. The authors hypothesized that there is a relationship between consumer awareness of the concept of sustainable consumption and the consumption of organic products. Consumer awareness means making conscious choices based on the knowledge expressed in the attitudes and, sometimes, preferences of the food brand. The research was conducted using a proprietary survey questionnaire. A total of 1067 respondents participated. A statistical analysis was performed by using Statistica 13.1 PL software, which includes descriptive statistics, the discriminant function analysis, and regression analysis. Motives were identified that are of crucial importance to the consumer deciding to purchase organic products. These include: beneficial health effects, contents of nutrients, no additional substances used in food production, taste, and others. A statistical relationship was established between environmental awareness and the tendency to buy organic products. Among the organic products, eggs, fresh fruit and vegetables, honey, cow’s milk and its derivatives, as well as cereal products, are the most preferred by consumers of both genders. The proposed model, which outlines the relationship between environmental awareness and the tendency to buy organic products, includes the following variables: care for the environment and animal welfare, no harmful substances used in food production, low level of processing, short shelf life.